2017
DOI: 10.1098/rsos.170896
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of dynamic material properties of intact rocks using seismic wave attenuation: an experimental study

Abstract: The mechanical properties of any substance are essential facts to understand its behaviour and make the maximum use of the particular substance. Rocks are indeed an important substance, as they are of significant use in the energy industry, specifically for fossil fuels and geothermal energy. Attenuation of seismic waves is a non-destructive technique to investigate mechanical properties of reservoir rocks under different conditions. The attenuation characteristics of five different rock types, siltstone, shal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 43 publications
(66 reference statements)
1
13
0
Order By: Relevance
“…These smaller scale fractures usually release AE signals with high frequency. Therefore, for granite, marble, and limestone, the signal peak frequencies larger than 300 kHz are in the majority, whereas for sandstone, the high frequency component of AE signal will be greatly attenuated due to high porosity [46][47][48][49], thus resulting in relatively larger proportion of low frequency signals being collected.…”
Section: Peak Frequency Distributionmentioning
confidence: 99%
See 1 more Smart Citation
“…These smaller scale fractures usually release AE signals with high frequency. Therefore, for granite, marble, and limestone, the signal peak frequencies larger than 300 kHz are in the majority, whereas for sandstone, the high frequency component of AE signal will be greatly attenuated due to high porosity [46][47][48][49], thus resulting in relatively larger proportion of low frequency signals being collected.…”
Section: Peak Frequency Distributionmentioning
confidence: 99%
“…Rock AE signal frequency has a close relationship with its internal crack scale, by constructing the relevant earthquake model and simulating the earthquake process in the laboratory. It is concluded that the rupture scale (or magnitude) M 0 is proportional to the −3 power of the frequency f. The scaling relation of size-frequency can be used to estimate the scale of the source of different frequency signals [12,48,49], and the relationship between source scale and frequency can be as follows [50]:…”
Section: Micromorphology Of Split Surfacementioning
confidence: 99%
“…Based on works of Castagna and Smith () and Wanniarachichi et al . (), the approximate ranges of these coefficients are λ[3,20] GPa and μ[1,30] GPa , where GPa are gigapascals. However, taking into consideration that the values of λ that are close to 0 might cause the issue within Backus averaging (Bos et al .…”
Section: Response Of Anisotropy Parameters To Changes Of λ and μmentioning
confidence: 99%
“…We examine only the ranges of Lamé coefficients that are relevant to sandstones (brine sands, gas sands and others). Based on works of Castagna and Smith (1994) and Wanniarachichi et al (2017), the approximate ranges of these coefficients are λ ∈ [−3 , 20] GPa and μ ∈ [1 , 30] GPa, where GPa are gigapascals. However, taking into consideration that the values of λ that are close to 0 might cause the issue within Backus averaging (Bos et al 2018;Kudela and Stanoev 2018), we set the ranges to be λ ∈ [3 , 20] GPa and μ ∈ [1 , 30] GPa.…”
Section: R E S P O N S E O F a N I S O T R O P Y P A R A M E T E R S mentioning
confidence: 99%
“…The cross-section has 6 sedimentary layers. We digitised the cross-section and converted the depth information from two-way time (seconds) to km using average speed of seismic waves in various lithologies multiplied by time, which gives layer thicknesses (Toksoz et al, 1976;Wanniarachchi et al, 2017). We then calculated the depth of the stratigraphic layer boundaries (Figure 1), followed by the collection of sedimentary layer features for example; lithology, absolute age, porosity, and many others as listed in Table 2, below.…”
Section: Datamentioning
confidence: 99%